CRIMINAL POLCY LOKIKA SANGGRAHA DALAM PERSPEKTIF HUKUM PIDANA INDONESIA - Saputra, Trias; Nugraha, Yudha Adhi (IBLAM LAW REVIEW, 2023)
Criminal Policy in criminal law or commonly known as Criminal Police is the attitude of a country in implementing criminal law in a country. Every Country Has a Different Criminal Policy, especially if it is related to religion and decency. In Balinese custom, it is known as the Lokika Sanggraha delict, a delict concerning decency which is highly trusted by the Balinese people. The offense gives high respect to women. In practice, there are many women who become victims of sexual violence that have not been accommodated through the National Criminal Law. This research will review the Lokika Sanggraha Criminal Policy which can be applied nationally through the Criminal Policy. This study uses a normative juridical approach that uses legal data